2011
DOI: 10.1039/c0jm03405c
|View full text |Cite
|
Sign up to set email alerts
|

Role of photoactive layer morphology in high fill factor all-polymer bulk heterojunction solar cells

Abstract: We report on the realization of all-polymer solar cells based on blends of poly(3-hexylthiophene-2,5-diyl) (P3HT) as a donor and poly{[N,N 0 -bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximide)-as an acceptor. High fill factors are demonstrated for the first time in this class of devices suggesting high dissociation efficiency for the bounded electron-hole pairs and balanced electron and hole mobility along the thin films. The use of the high-mobility n-type P(NDI2OD-T2) polymer enables us to overcome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
136
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(148 citation statements)
references
References 42 publications
11
136
1
Order By: Relevance
“…28 Consequently, the earlier reports on the all-PSC measurements of P3HT/P(NDI2OD-T2) blend showed very low device efficiency value (PCE, 0.2%). 29,30 Later studies showed that the aggregation in P(NDI2OD-T2) could be suppressed significantly in the early stage of film formation by using more polar aromatic solvents. 31 Indeed, the solar cell devices prepared from such nonaggregated solution showed improved PCE due to good intermixing of donor and acceptor components, thereby efficiently harvesting photogenerated excitons at donor−acceptor interface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…28 Consequently, the earlier reports on the all-PSC measurements of P3HT/P(NDI2OD-T2) blend showed very low device efficiency value (PCE, 0.2%). 29,30 Later studies showed that the aggregation in P(NDI2OD-T2) could be suppressed significantly in the early stage of film formation by using more polar aromatic solvents. 31 Indeed, the solar cell devices prepared from such nonaggregated solution showed improved PCE due to good intermixing of donor and acceptor components, thereby efficiently harvesting photogenerated excitons at donor−acceptor interface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The well-known composite of P3HT and a fullerene derivative, PCBM, has little absorptivity in the NIR region longer than 650 nm. Therefore, a variety of LBPs have been synthesized, consequently, being available for choosing polymers with a preferable bandgap and adequate HOMO/LUMO potentials as electron donor and acceptors [9][10][11]. The absorption spectrum of N2200 in Fig.…”
Section: P3ht/n2200 and P3ht/n2200/sinc Blendsmentioning
confidence: 99%
“…Some approaches have been tested to control the nanoscale film morphologies of polymer/PCBM blends. [33][34][35][36] The addition of a compatibilizer to suppress large-scale phase separation of the polymer/PCBM blend can enhance the long-term thermal stability of the cell performance. 33 Incorporating electron acceptors with high mobility in the polymer/PCBM blend film can result in highly balanced electron and hole mobilities, thereby enhancing the PV performance of the PSC.…”
Section: Introductionmentioning
confidence: 99%
“…33 Incorporating electron acceptors with high mobility in the polymer/PCBM blend film can result in highly balanced electron and hole mobilities, thereby enhancing the PV performance of the PSC. 34 Light-or solvent-soaking to tailor the morphology of the active layer is another potential approach toward improving the PV stabilities of PSCs. 35,36 On the other hand, decreased PV efficiency stability is closely related to the degree of thermally induced aggregation of the polymer chains and PCBM units.…”
Section: Introductionmentioning
confidence: 99%